O suicídio entre adolescentes no município de Barreirinha – AM: uma questão de saúde pública - Costa, Irnan Carneiro (Brasil, 2024)
This study aimed to identify the factors that influence the incidence of suicide among adolescents in the municipality of Barreirinha, located in the state of Amazonas, considering this phenomenon as a public health issue. The increase in suicide cases in this age group has raised serious questions about the mental health and quality of life of young people in the region. The study in question is based on local epidemiological data and qualitative analyzes to draw a comprehensive overview of the current situation. Furthermore, existing public policies and the gaps that need to be filled to ensure na effective and integrated approach to combating suicide among adolescents are explored. The immediate results demonstrate the need to create listening spaces and implement health and life protection programs aimed at the adolescent population in Barreirinha.